Snow cover evolution at Qasigiannguit Glacier, southwest Greenland: A comparison of time-lapse imagery and mass balance data - Messerli, Alexandra; Arthur, Jennifer; Langley, Kirsty; How, Penelope; Abermann, Jakob (Frontiers in Earth Science, 2022)
In a warming climate, understanding seasonal fluctuations in snowline position is key to accurately predicting the melt contribution of glaciers to sea-level rise. Snow and ice conditions have a large impact on freshwater availability and supply on seasonal and multi-annual timescales. Factors such as snow extent and physical characteristics aﬀect predictions in snowmelt- and glacier-fed catchments, influencing the potential of hydropower and drinking water supply in these areas, as well as ecosystems and fjord waters. Summer snow monitoring on glaciers and ice caps peripheral to the Greenland Ice Sheet are limited, and are typically excluded from ice-sheet wide assessments. Here, we analyse snow extent evolution on Qasigiannguit Glacier (QAS), a small coastal mountain glacier in Kobbefjord, southwest Greenland, with the aim of obtaining a baseline dataset of snow and ice conditions. Maximum snowline altitude and bare ice extent are extracted using terrestrial time-lapse photogrammetry, and compared to mass balance and automated weather station observations since 2014. The number of days of visible bare ice, cumulative Positive Degree Days (PDD) and mass balance are closely linked; with 2016 and 2019 experiencing the most negative mass balance, earliest onset of PDDs and greatest cumulative PDDs. 2021 had a relatively small negative mass balance (-0.072 m w.e.) despite having the longest bare ice exposure (112 days). This is attributed to the timing of bare ice exposure relative to the mean 90% cumulative PDD (28th August). Longer periods of bare ice exposure precede the mean 90% cumulative PDD in both 2016 and 2019, which reflects differences in the amount of melt energy available at different times in the melt season. This has far reaching implications for mass balance modelling efforts as this study demonstrates that spatial and temporal variability in snow/bare ice cover are linked to differences in melt factors and energy required to melt snow and ice. Snowline position provides a coarse indication of surface conditions, but future modelling efforts need to incorporate the complex spatial evolution of snow-to-bare ice ratios in order to improve estimates of mass loss from glaciarised mountain catchments.